UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) KELAS IV SD N 101212 PADANG BUJUR - Yulia Anita Siregar (Universitas Islam Sumatera Utara, 2018)
Abstract. This study aims to improve the learning outcomes of Mathematics students in grade IV SD N 101212 Padang Bujur. This study uses Classroom Action Research (CAR) type of collaboration with steps of planning, action, observation, and reflection consisting of two cycles. Data collection techniques used are test, non-test, and documentation. Adapaun indicator of success of this study is 85% of all students got a value of ≥ 75. The results of the study were analyzed by completeness analysis. In the teaching and learning process using the cooperative type NHT learning model, in cycles 1 and 2 Mathematics learning outcomes increased. Of the students with 15 children, when the pre-cycle students were completed there were 5 (33.33%). Whereas 10 students (66.66%) did not complete. After conducting classroom action research using the NHT cooperative learning model in the first cycle the students who completed the study numbered 8 students (53.33%) while the incomplete ones in the study were 7 students with an average score of 73.66. In the second cycle, students who completed learning were 13 students (86.66%), while those who did not complete the study were 2 students (13.33%) with an average score of 81.33. The results of this study indicate that through the NHT cooperative learning model can improve Mathematics learning outcomes for students in Class IV SD N 101212 Padang Bujur.Keywords: Cooperative learning model Number Head Together (NHT) type, Mathematics Learning Outcomes